Ber and Snr Based Physical Layer Security Analysis with Cooperative Jamming - Valencia-Cordero, C (Institute of Electrical and Electronics Engineers Inc., 2021)
Physical layer security has been widely studied by the scientific community from a theoretical point of view, but the lack of practical metrics that can deliver a quick and easy-to-read response for the communications engineer makes it difficult to implement this type of security in current technologies. That is why this article proposes two practical metrics derived from the Bite error rate (BER) vs Signal to noise ratio (SNR) that quantify the security against the eavesdropper and the readability of the message in the legitimate receiver, finding a feasible power distribution for transmission. © 2021 IEEE.